Sunday Drivers, or Too Fast and Too Furious? - Juan Francisco (Frank) Arellano; Kevin Fang (Findings)
The recent influx of electric scooters (e-scooters) has left cities scrambling to answer how to best to regulate them. To help inform policymaking, we studied e-scooter riding behavior through observations of speed and rider distractions. Observations show e-scooter riders travel faster on streets and slower on sidewalks and slightly slower than cyclists on streets. Additionally, few e-scooter riders wear helmets, and some may be distracted by headphones but not by handling cellphones.